Maraval Road - Trinidad - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2009)
Large, leafy trees, whose foliage cross one another to form a thick black mass, and three large clumps of bamboo stand stately off to the left of the earthen road. The long, lean stalks of the bamboo overlap each other as they reach skyward. The road looks even, without holes, and wide. A four wheeled, horse and carriage (or horse and buggy) and a donkey cart traverse the road. The horse and carriage was a light, simple, two-person carriage popular in the 19th and early 20th centuries. Some carriages had tops. This one has a large, black, shiny, folded top. The huge wheels were usually about forty-four inches in diameter and they were often covered in rubber. One or two horses could be harnessed to them to tow the carriage and passenger or passengers along. A donkey cart, usually used in rural transport for agricultural purposes, generally had two oversized wheels attached to a wooden cart which was drawn by one or two donkeys. In this image the horse and carriage and the donkey cart are about to pass one another. There is one person in each vehicle. The head of the person riding in horse and carriage can be seen, towering above the folded top in the forefront of the photograph. The one person in the donkey cart, appears to be a man. He is wearing a hat and is sitting slightly slouched to one side of his seat as he totes cut grass. Behind him, to the left of the road, is a pole that has a “T-shaped” head and may be for a street sign as no electricity lines are visible. There is a mound of leaves heaped off to the left of the road. It might have been customary to pile leaves along the road side in this manner. A United States of America, one cent postage stamp featuring Ben Franklin is attached to the postcard and has been stamped Jan 7, 8 a.m. 1908.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bamboo--Trinidad and Tobago; Rural roads--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; 1908